2021
DOI: 10.37394/232015.2021.17.79
|View full text |Cite
|
Sign up to set email alerts
|

Research and Development Spillover, Irrigation Water Use and Agricultural Production in Pakistan

Abstract: This research entails investigation of the impacts of Research and Development (R&D) spillover and irrigation water use efficiency on agricultural productivity in Pakistan. Influenced through the importance of R&D spillovers in innovation, water scarcity, irrigation technology, internal and external R&D shocks, human capital, agriculture employment and land were analyzed in the agricultural productivity. Considered the research objectives the annual timeseries data is collected for the period of 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Tube well (TWL) short-run impacts on maize production (MZP) are statistically significant at the 1 % level (coefficient = −16.796, p-value = 0.004). This study confirms [ [ 66 , 79 ]] that tube wells have a short-run impact on maize productivity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Tube well (TWL) short-run impacts on maize production (MZP) are statistically significant at the 1 % level (coefficient = −16.796, p-value = 0.004). This study confirms [ [ 66 , 79 ]] that tube wells have a short-run impact on maize productivity.…”
Section: Discussionsupporting
confidence: 88%
“…This literature review aims [ 65 ] to examine the existing data on how CO2 affects maize output in Pakistan against the backdrop of global warming. According to an empirical study, there will be both beneficial and detrimental consequences of increased atmospheric CO2 levels on maize output [ 66 ]. On the one hand, increased CO2 levels can increase maize production by stimulating photosynthesis and growth [ 67 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The magnitude value AL t highlights that agriculture land holds a higher share in ATFP t growth and reduction in cultivation land reduces the agriculture productivity. Urbanization is the reason for a reduction in cultivation land and lowering of the agriculture share of GDP [53], creating food security challenges in Pakistan. The outcomes of the study are consistent with the findings of Villoria [48], who empirically found the increase in cropland area to be an agriculture productivity input to increase the ATFP t growth.…”
Section: Ardl Estimatesmentioning
confidence: 99%
“…The higher value of ECM (−1) revealed that if there is a disequilibrium in R&D input, adoption and input shocks can be adjusted with higher speed during the given period. The agriculture R&D innovation inputs perform an essential role in bringing ATFP t into its steady-state position [53]. The ECM t (−1) coefficient value is higher due to two cropping seasons (Rabi and Kharif) in Pakistan, with heterogeneously located areas, so if the production of one crop is lower, its production deficiency will recover either during the same crop or during the next crop [53,61].…”
Section: Ardl Estimatesmentioning
confidence: 99%